GEODYNAMICS OF DOBROGEA (ROMANIA): NEW CONSTRAINTS ON THE EVOLUTION OF THE TORNQUIST-TEISSEYRE LINE, THE BLACK SEA AND THE CARPATHIANS - Hippolyte J.-C. (My University, 2002)
Dobrogea is the only place south of Poland where the Tornquist–Teisseyre Line, Europe's longest lineament, outcrops. To characterize and date the tectonic activity of this line and to understand its relations with the neighboring structures, e.g. the Carpathians and the Black Sea Basin, the fracturing of Late Jurassic to Neogene rocks in north, central, and south Dobrogea is analyzed. These paleostress reconstructions indicate that the Dobrogea Orogen was built under a N–S compression, with strain partitioning between thrusting at its front and dextral–reverse slip along the Peceneaga–Camena and Capidava–Ovidiu Faults during the Late Jurassic–Barremian. From Aptian to Coniacian, the Dobrogea platform was characterized by SE-directed extension compatible with the Aptian–Cenomanian rifting of the western Black Sea, followed by the SE-directed drifting of a part of the Moesian Block (i.e. the Istanbul block). On its southern extremity, the Tornquist–Teisseyre Line does not show evidence for any large-scale Alpine strike-slip movements (postulated by many), the Peceneaga–Camena Fault being reactivated in Latest Cretaceous–Paleogene as a pure reverse fault. During the Late Tertiary, the Carpathian compression was poorly transmitted to Dobrogea. Extension dominated the Neogene deformation, which indicates a weak coupling between the Carpathians and its foreland.